Decision aids for patients considering total joint replacement: a cost-effectiveness analysis alongside a randomised controlled trial. Issue 10 (October 2017) - Trenaman, L.; Stacey, D.; Bryan, S.; Taljaard, M.; Hawker, G.; Dervin, G.; Tugwell, P.; Bansback, N.
Summary: Background: Shared decision-making (SDM) is a key priority to improve patient-centred care, and can play an important role in helping patients decide whether to undergo total joint arthroplasty (TJA). Patient decision aids can support SDM; however, they may incur an upfront cost. We aimed to estimate the health and economic effects of patient decision aids for TJA. Methods: A cost-effectiveness analysis of a randomised controlled trial (RCT) with 2-year follow-up. 343 patients were recruited from two orthopedic screening clinics in Ottawa, Canada. Patients were randomized to either a patient decision aid plus surgeon preference report (decision aid) or usual care. Primary outcomes were costs (in 2014 CAD$), quality-adjusted life-years (QALYs), and the incremental cost-effectiveness ratio (ICER). Costs were calculated by multiplying self-reported resource use by unit costs. QALYs were calculated by mapping the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) to EuroQol 5-Dimension (EQ-5D) health utilities. Costs and QALYs were discounted at 5%. Multiple imputation was used to handle missing data, and bootstrapping was used to estimate uncertainty. Results: The sample comprised 167 intervention and 167 control group patients. The decision aid arm had fewer surgeries over the 2-year period thereby incurring a negative incremental cost of −$560 (95% CI: −$1358 to $426) per patient while providing 0.05 (95% CI: −0.04 to 0.13) additional QALYs per patient. Consequently, the decision aid arm was dominant. Conclusion: The use of a patient decision aid was associated with fewer health care costs, while producing similar health outcomes. Clinical trial registration number: CT00911638 (clinicaltrials.gov ).